EMOSI POSITIF PADA GURU PENDAMPING SISWA AUTIS PADA SD NEGERI 131/IV KOTA JAMBI: POSITIVE EMOTIONS IN TEACHERS ASSISTANCE FOR AUTISTIC STUDENTS AT SD NEGERI 131/IV JAMBI CITY - Agnes Rianty; Dessy Pramudiani (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2021)
Introduction Autistic students had the same rights as normal students in obtained education. Inclusive school are needed for autistic students. Inclusive schools need teacher assisting for accompany the learning process of students with autism. Autistic students had excessive behaviour disorder; self-harm, aggression, and tantrums. The teacher assisting students with autism often feels angry and annoyed when accompanying students with autism. Positive emotions were things that can balanced the emotions of teachers assistance for autistic students in carried out their profession. To find out how to describe positive emotions and the factors that influence the formation of positive emotions in the teachers assistant for autistic students at SD Negeri 131/IV Jambi City. Method Qualitative method with a phenomenological approach. The data was collected use an observation, documentation and in-depth interviews. Use Interpretative phenomenological analysis (IPA). The characteristic of the participant teacher accompanying students with autism in SD Negeri 131/IV Jambi City, aged 25-55 years, faced autistic students directly, and had worked for at least 3 years. Result An overview the positive emotions in the teacher assistant for autistic students at SD Negeri 131 / IV Jambi City were feels of joy, self-satisfaction, attraction, love, fighting spirit, gratitude, and sympathy. The influence factors consist of environment, cooperation, selfefficacy, work experience, internal motivation, and personality. Conclusion And Recommendation The four participants have described positive emotions that are able to balance all emotions within themselves for their life and work. This research wasexpected to add insight into positive emotions. Keywords Positive emotions, teacher assistant, autistic students ABSTRAKPendahuluan Siswa autis memiliki hak yang sama dengan siswa normal dalam memperoleh pendidikan. Sekolah inklusi dibutuhkan untuk siswa autis. Sekolah inklusi memerlukan guru pendamping untuk mendampingi proses belajar siswa autis. Siswa autis memiliki gangguan perilaku berlebihan; melukai diri sendiri, agresif, dan tantrum. Guru pendamping siswa autis kerap merasakan emosi marah dan kesal saat mendampingi siswa autis. Emosi positif menjadi hal yang bisa menyeimbangkan emosi guru pendamping siswa autis dalam menjalani profesinya. Tujuan Untuk mengetahui bagaimana gambaran emosi positif dan faktor yang mempengaruhi pembentukan emosi positif pada guru pendamping siswa autis di SD Negeri 131/IV Kota Jambi. Metode Metode kualitatif dengan pendekatan fenomenologi. Metode pengumpulan data menggunakan observasi, dokumentasi dan wawancara mendalam. Menggunakan interpretative phenomenilogical analysis (IPA). Karakteristik partisipan guru pendamping siswa autis di SD Negeri 131/IV Kota Jambi, berusia 25-55 tahun, menghadapi secara langsung siswa autis, dan sudah bekerja minimal 3 tahun. Hasil Gambaran emosi positif pada guru pendamping siswa autis di SD Negeri 131/IV Kota Jambi adalah perasaan gembira, kepuasan diri, ketertarikan, cinta, berdaya juang, kebersyukuran, dan simpati. Faktor yang mempengaruhi terdiri dari lingkungan, kerja sama, kemampuan diri, pengalaman kerja, motivasi internal, dan kepribadian. Kesimpulan Dan Saran Keempat partisipan telah menggambarkan emosi positif yang mampu menyeimbangkan segala emosi dalam dirinya. Penelitian ini diharapkan mampu menambah wawasan mengenai emosi positif. Kata kunci emosi positif, guru pendamping, siswa autis